Mirror therapy in upper limb rehabilitation after Stroke - Sónia Catarina Cabete de Freitas; Clara Maria Ângelo Rodrigues; Luís Filipe Picôas Pratas; Susana Isabel Faria de Almeida (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction:The loss of motor function in the upper limbs is one of the most debilitating deficits after a cerebrovascular accident (CVA). Mirror Therapy (MT) is a promising approach that aims to improve motor learning and promote neural reorganization through different afferent inputs and visual feedback patterns. Goal:Identify the gains obtained by the intervention of the rehabilitation nurse through an MT protocol. Method: This is a case study, with an experimental design of a single case, where a male, 78 years old, left hemiparesis, due to ischemic stroke, with good cognitive capacity, was selected. Intervention protocol consisting of 15 sessions, lasting 30 minutes, where MT is implemented. The instruments used were: Mini Mental State Examination Questionnaire (MMSE); Motor Activity Log Scale (MAL); Disabilities of the Arm, Shouder and Hand (DASH) and the Hand Movement Scale (HM). Results: An improvement was observed through the gain of independence and motor skill in the paretic upper limb after stroke, after intervention with MT. Discussion:The evaluated patient evidenced motor improvement during activities of daily living (ADL). This result is corroborated by other studies on the application of MT and the use of motor imagery after stroke. Conclusion: MT generated positive effects on the motor function of the evaluated patient.